Thirty-year trends in the prevalence of cardiometabolic risk factors in the populations of the Russian Federation and the United States of America - V. G. Vilkov; S. A. Shalnova (Кардиоваскулярная терапия и профилактика)
Aim. To study trends in the prevalence of hypertension (HTN), obesity, elevated non-high-density lipoprotein cholesterol (non-HDL cholesterol) levels in Russia and the USA from 1975 to 2014.Material and methods. According to the data of cross-sectional population studies in Russia and the USA in 1975-1982 and 2007-2014, the prevalence of risk factors (RFs) in men and women aged 25-64 was studied. The data of Lipid Research Clinics studies, Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation (ESSE-RF) study, as well as data from National Health And Nutrition Examination Survey (NHANES) studies (USA) were used. The total number of persons analyzed was 41268. The proportion of individuals with risk factors and 95% confidence interval were calculated.Results. In the 1980s, the prevalence of studied RFs in Russia and the United States did not differ in most sex and age groups. Over the next 30 years, both populations are characterized by a decrease in the prevalence of HTN and elevated non-HDL cholesterol (≥ 3.7 mmol/l) and an increase in the prevalence of obesity. In 2012, HTN in men and women in Russia occurred more frequently than in the United States. Obesity was less common in men and women 25-44 years old in Russia and in women >54 years old in the USA. The prevalence of non-HDL cholesterol ≥3,7 mmol/l in Russia compared with the United States was higher in people >44 years old and lower in women 25-34 years old.Conclusion. In the 1980s, there were no differences in the prevalence of cardiometabolic risk factors in Russia and the United States. In the 2010s, HTn and partly dyslipidemia were more common in Russia, and the prevalence of obesity in young and middle-aged people was higher in the United States.